In this case, we'll have to carry out several steps to find the solution.
Step 01:
Data:
x^4 + 6x^3 + 6x^2 + 6x +5=0
roots = ?
Step 02:
a. possible rational roots
rational root theorem:
possible rational roots = factors of the constant / factors of the lead
x^4 + 6x^3 + 6x^2 + 6x + 5=0
lead = 1
constant = 5
factors of the coefficient, 1 are ±1
factors of the constant term, 5 are ±1 , ±5
possible rational roots = (±1 , ±5) / ±1
possible rational roots = ±1 , ±5
Step 03:
b. synthetic division
possible rational root:
(x + 1) ===> x = - 1
-1 | 1 6 6 6 5
| -1 -5 -1 - 5
------------------------------
1 5 1 5 0
The remainder is 0
Step 04:
c. solve the equation
x = -1
x^4 + 6x^3 + 6x^2 + 6x + 5 = 0
![\begin{gathered} (-1)^4+6(-1)^3+6(-1)^2+6(-1)+5=0 \\ 1\text{ - 6 + 6 - 6 + 5 = 0} \\ 0\text{ = 0 } \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/i64ue0hidonhvbr6oltg7u9jy821pfhbap.png)
That is the full solution.